In Situ Synthesis and Cell Line Studies of Nano-Hydroxyapatite/Graphene Oxide Composite Materials for Bone Support Applications - Özder, Melike Nur; Çiftçi, Fatih; RENCÜZOĞULLARI, ÖZGE; Arısan, Elif Damla; Üstündağ, Cem Bülent (Elsevier Science Ltd., 2023)
The current work presents and discusses the findings of on the structural, chemical and thermal properties of in situ synthesis of graphene oxide-hydroxyapatite (GO/HA) nanocomposite materials doped with graphene oxide (w/w) at different ratios of 0%, 0.1%, 0.5% and 1% for bone tissue support applications. Microstructure and crystallinity were investigated by Fourier transform infrared spectroscopy (FT-IR), Raman spectroscopy, X-ray diffraction (XRD), thermogravimetric analysis (TGA), pore structures by Brunauner-Emmett-Teller (BET) analysis, Dynamic light scattering (DLS). Transmission electron microscopy (TEM) and scanning electron microscopy (SEM) were performed to characterize the morphology of the bone support scaffold materials. The attachment and cell viability of fibroblast NIH/3T3 cells were observed on the synthesized bone support composite materials. Excellent proliferation of bone support scaffolds containing 0.5% and 1% GO (w/w) was observed by fluorescence microscopy using 3,3 & PRIME;-Dihexyloxacarbocyanine iodide (Dio-6), 4 & PRIME;,6-diamidino-2-phenylindole (DAPI), MitoRed and Anti-Vinculin. The innovative materials revealed in this study demonstrated that GO and HA promoted cell proliferation and cell adhesion with their well-compatible properties and helped cell penetration and colonization by increasing the surface area of GO, making them promising materials for bone support applications.
Keywords: Bone Tissue Engineering; Graphene Oxide; Hydroxyapatite; Nanocomposite